Targeting the bone marrow niche, moving towards leukemia eradication - Semedo, Carla; Caroço, Raquel; Almeida, António; Cardoso, Bruno António (Frontiers in Hematology, 2024)
Hematopoiesis is a complex and tightly regulated process that drives the formation of mature blood cells from a single hematopoietic stem cell. This complex process occurs within the bone marrow, which, once disrupted or deregulated, subverts normal hematopoietic development, allowing leukemic cells to emerge, proliferate, and thrive. Notably, several cellular populations and paracrine factors within the bone marrow fuel leukemia expansion and progression. This review presents an overview of the main microenvironmental components that promote myeloid leukemia progression, discussing the emerging therapeutical strategies that target both leukemic cells and the supportive bone marrow microenvironment – targeting both the seed and the soil.